Evaluating status of European eel (Anguilla anguilla) in Skadar Lake - Mrdak, Danilo; Đurović, Mirko; Laušević, Radoje (Institute of Marine Biology, University of Montenegro, 2020)
Evaluation of status of the European Eel ( Anguilla anguilla ) in Montenegrin part of theSkadar Lake.